How do I solve 2z=12-14 for z?

6 Answers | Add Yours

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

Th equation 2z = 12 - 14 has to be solved for z.

2z = 12 - 14

both the terms on the right hand side are numbers and 14 can be subtracted from 12 to give -2.

=> 2z = -2

divide both the sides by 2

=> z = -2/2

=> z = -1

The solution of 2z = 12 - 14 is z = -1.

zumba96's profile pic

zumba96 | Student, Grade 11 | (Level 3) Valedictorian

Posted on

2z=12-14

Isolate z first 

Since it is already isolated combine like terms

2z=-2

Divide by 2

z=-1

jess1999's profile pic

jess1999 | Student, Grade 9 | (Level 1) Valedictorian

Posted on

2z = 12 - 14

To solve this equation for z, first subtract 12 with 14

By doing that your equation should look like

2z = -2    now divide 2 on both sides

By dividing 2 on both sides your equation should look like

z = -1 which is your answer

Wiggin42's profile pic

Wiggin42 | Student, Undergraduate | (Level 2) Valedictorian

Posted on

2z = 12 - 14

Simplify the right side by combining the like terms. Make note of the signs. : 

2z = -2

Isolate the z. To do this, we have to undo the multiplication by using division. Since z is multiplied by 2, we will divide both sides by 2: 

z = -1

atyourservice's profile pic

atyourservice | Student, Grade 11 | (Level 3) Valedictorian

Posted on

 2z = 12 - 14 for z

first combine like terms  12 - 14 = -2

2z = - 2

since we are solving for z we have to get z by itself and in order to do that we have to divide by 2

`( 2 z ) / 2 = (- 2 )/2`

z=-1

tvxqx3's profile pic

tvxqx3 | Student, Grade 9 | eNotes Newbie

Posted on

2z = 12 - 14

You can start by 12 minus 14 which equals -2.

Then, you have this equation: 2z = -2.

Finally, you divide by 2 to both sides. (2z/2 = -2/2)

You get: z = -1.

That's one way you can solve this problem.

The other way is like this:

2z = 12 - 14

You can divide by 2 first.

z = 12/2 - 14/2

Since there are fractions you can simplfy it.

If you simplfy it, you get:

z = 6 - 7

Which equals: z = -1

 

So you have two ways to solve that problem.

We’ve answered 318,928 questions. We can answer yours, too.

Ask a question